Increasing Type 1 Poliovirus Capsid Stability by Thermal Selection - Adeyemi, Oluwapelumi O. (J Virol, 2017)
Poliomyelitis is a highly infectious disease caused by poliovirus (PV). It can result in paralysis and may be fatal. Integrated global immunization programs using live-attenuated oral (OPV) and/or inactivated (IPV) PV vaccines have systematically reduced its spread and paved the way for eradication. Immunization will continue posteradication to ensure against reintroduction of the disease, but there are biosafety concerns for both OPV and IPV. They could be addressed by the production and use of virus-free virus-like particle (VLP) vaccines that mimic the “empty” capsids (ECs) normally produced in viral infection. Although ECs are antigenically indistinguishable from mature virus particles, they are less stable and readily convert into an alternative conformation unsuitable for vaccine purposes. Stabilized ECs, expressed recombinantly as VLPs, could be ideal candidate vaccines for a polio-free world. However, although genome-free PV ECs have been expressed as VLPs in a variety of systems, their inherent antigenic instability has proved a barrier to further development. In this study, we selected thermally stable ECs of type 1 PV (PV-1). The ECs are antigenically stable at temperatures above the conversion temperature of wild-type (wt) virions. We have identified mutations on the capsid surface and in internal networks that are responsible for EC stability. With reference to the capsid structure, we speculate on the roles of these residues in capsid stability and postulate that such stabilized VLPs could be used as novel vaccines. IMPORTANCE Poliomyelitis is a highly infectious disease caused by PV and is on the verge of eradication. There are biosafety concerns about reintroduction of the disease from current vaccines that require live virus for production. Recombinantly expressed virus-like particles (VLPs) could address these inherent problems. However, the genome-free capsids (ECs) of wt PV are unstable and readily change antigenicity to a form not suitable as a vaccine. Here, we demonstrate that the ECs of type 1 PV can be stabilized by selecting heat-resistant viruses. Our data show that some capsid mutations stabilize the ECs and could be applied as candidates to synthesize stable VLPs as future genome-free poliovirus vaccines.